A Novel Close Loop Analysis of Gamma Prototype Stirling Engine - Abdul Rab Asary; Basit Abdul; Abdul Samad; Mohammad Abul Hasan Shibly (Engineering Proceedings, 2023)
Air pollution is greatly influenced by the emissions generated by automotive engines, making it a pressing concern. To address this issue, a considerable amount of research is currently devoted to recovering waste heat from these engines. A gamma-type Stirling engine has been meticulously chosen to achieve this specific objective. This study elucidates a new isothermal method that effectively analyses Stirling engines. A set of differential equations is proficiently solved by employing the powerful MATLAB R2020a software. Remarkably, the simulation results obtained from this computational approach closely align with the experimental data, indicating the accuracy and reliability of the methodology. Furthermore, this research delves into the feasibility of employing the Stirling engine as a Combined Cooling, Heating and Power (CCHP) system, shedding light on its potential applications in various domains.